Estratégias de leitura com o gênero discursivo tirinha: uma experiência no 7º ano do ensino fundamental - Morais, Aucilene Alves de (2020)
The development of reading competence is essential for students of Basic Education, as reading, as an instrument of social insertion and discovery, enables the acquisition and expansion of knowledge, which allows to see the world critically and act on it autonomously. However, the training of a proficient reader still represents a major challenge in the Basic Education school, more specifically, in Portuguese Language classes in Elementary School. In the routine of our teaching, we found that reading teaching practices have not been developed effectively in this teaching stage, compromising the training of young readers as active subjects capable of giving meaning to what they read. In addition, most of the students have a lack of interest in reading, and when they are willing to do so, they demonstrate difficulty in understanding, however simple the text may be. Based on these assumptions, the main objective of our work was to develop an intervention project to teach students how to use reading strategies based on the comic strip genre. For this, as a theoretical contribution, we resort to the conceptions of reading by the authors Koch and Elias (2008), Bonifácio (2015), Cavalcante (2013). With regard to reading strategies, we are anchored in Solé (1998) and Kleiman (2002); for discursive genres, we endorse Bakhtin (1997) and Marcuschi (2008); on the comic strip, we highlight the research by Nicolau M (2007) and Nicolau V (2013); and we still observe the official curricular guidelines for Elementary Education, such as the National Curriculum Parameters for Portuguese Language - PCN-LP (1998) and the Common National Base, Curricular - BNCC (2017). In relation to the methodology, our research is of an applied nature and of an interventionist character, characterized as an action research, with a predominantly qualitative approach. The reading project was organized in four stages: presentation of the reading project and the discursive genre and the application of oral and written activities, using the strategies of the moments before, during and after reading the strips. Thus, the results of the corpus analysis, consisting of a set of activities applied to students in the 7th grade of elementary school at a municipal school in João Pessoa / PB, indicated that, after our intervention, there were significant advances, with regard to both the improvement of students' reading skills and the enrichment of the teacher's pedagogical practice.